Application of microwave heating with iron oxide nanoparticles in the in‐situ exploitation of oil shale. Issue 5 (16th August 2018) - Zhu, Jingyi; Yang, Zhaozhong; Li, Xiaogang; Qi, Shuangyu; Jia, Min
Abstract: On the basis of the microwave heating method combining with hydraulic fracturing for the in‐situ exploitation of oil shale, this article investigates the effects of iron oxide nanoparticles on the performance improvement of foamed pad fluid, heating efficiency enhancement under microwave irradiation and potential reservoir damage after microwave treatment. Different products were also analyzed under multiple heating parameters by using gas chromatograph‐mass spectrometer (GC‐MS), X‐ray diffraction (XRD), and scanning electron microscopy (SEM). Heating experiments showed that foamed pad fluid was better than water based pad fluid in terms of energy conservation. Results have demonstrated that iron oxide nanoparticles can not only increase nearly 75 seconds of half‐life of the foamed pad fluid, but also slightly enhance the viscosity of foamed pad fluid. Fast heating rate and energy saving were also accomplished by iron oxide nanoparticles. In the presence of iron oxide nanoparticles, it took less than 10 minutes for oil shale to reach 750°C at 1000 W, showing extremely low energy consumption. SEM experiment showed that microwave induced the creation of pores and micro fractures, and the retention of iron oxide nanoparticles inside the oil shale would not cause reservoir damage. By analyzing the products, it is recognized that reaction temperature and heating method had a great influence on the distribution of the noncondensable gases. The production of spent shale was controlled by heating method, reaction temperature, heating time, and output power. The results from this study are important to the in‐situ exploitation of oil shale and environmental protection. Abstract : This investigation combines microwave heating method, hydraulic fracturing, and nanotechnology together to efficiently in‐situ exploit oil shale and studies the effects of iron oxide nanoparticles and the production process during microwave heating, which is very novel. Iron oxide nanoparticles can not only enhance the performance of foamed pad fluid, but also efficiently help the transformation of oil shale under microwave irradiation.